The Fusion of Islamic Education and Bugis Socio-cultural Values as a Guide to Freedom of Thought - Muh. Ilham Jaya; Arfian Alinda Herman; Musmulyadi; Immanuel Conti Morales, Alberto (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
Background: The existence of sociocultural values that are so strong and thick in the daily life of Bugis people is interesting to be associated with the conception of freedom of thought. Considering that freedom of thought is still a concept that still requires a long study. Research Objectives: This research provides an overview of the conception of freedom of thought and how Bugis socio-cultural values and norms can guide this freedom of thought. Hopefully, this research will provide a comprehensive understanding of freedom of thought from the perspective of Islamic education and Bugis socio-culture. Methods: The research method used is a library research method that collects related literature and then combines it with content analysis so as to provide results and conclusions. Results: The results show that freedom of thought is a concept that refers to individual freedom to think independently and critically without being influenced by existing opinions or authorities. However, freedom of thought must be accompanied and "supervised" by a herd of values and a set of principles so that there will be no significant problems arising when the thinking touches the corners of axiology (intersects with social society). Conclusions: Islamic education and Bugis socio-cultural values can greatly guide freedom of thought because the development of Islam itself has recognized the school of kalam science as the foundation of thinking and Bugis society contains so many values, both from the oral tradition of pappaseng and those contained in the ethical philosophy called pangadereng.